2004
DOI: 10.1074/jbc.m405123200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Inhibition Promotes Desmosome Assembly and Strengthens Intercellular Adhesion in Squamous Cell Carcinoma Cells

Abstract: The epidermal growth factor receptor (EGFR) has been proposed as a key modulator of cadherin-containing intercellular junctions, particularly in tumors that overexpress this tyrosine kinase. Here the EGFR tyrosine kinase inhibitor PKI166 and EGFR blocking antibody C225, both of which are used clinically to treat head and neck cancers, were used to determine the effects of EGFR inhibition on intercellular junction assembly and adhesion in oral squamous cell carcinoma cells. EGFR inhibition resulted in a transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
136
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 50 publications
10
136
1
1
Order By: Relevance
“…Both cadherins were detected as early as 5 min and accumulated over time, the levels decreasing beginning at 90 min presumably due to degradation of the internalized pool and/or recycling back to the surface (Figure 2, B and C). Both full-length and a 100-kDa cell-retained Dsg2 fragment, previously shown to result from MMP-dependent processing of Dsg2 (Lorch et al, 2004), appeared in the internalized pool over a similar time course. Importantly, internalization occurred at calcium concentrations ranging from 0.09 to 1 mM, Figure 2.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Both cadherins were detected as early as 5 min and accumulated over time, the levels decreasing beginning at 90 min presumably due to degradation of the internalized pool and/or recycling back to the surface (Figure 2, B and C). Both full-length and a 100-kDa cell-retained Dsg2 fragment, previously shown to result from MMP-dependent processing of Dsg2 (Lorch et al, 2004), appeared in the internalized pool over a similar time course. Importantly, internalization occurred at calcium concentrations ranging from 0.09 to 1 mM, Figure 2.…”
mentioning
confidence: 67%
“…We have previously demonstrated that Dsg2 shedding occurs in an MMP-dependent manner (Lorch et al, 2004). Subsequently, ADAM10 was shown to shed N-and E-cadherin from the surface and reduce adhesion of neuronal and epithelial cells Reiss et al, 2005), and Dsg2 was recently identified by a proteomics approach as a substrate for both ADAM10 and 17 (Bech-Serra et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations